Schiotz Tonometry Accurately Measures Intraocular Pressure in Boston Type 1 Keratoprosthesis Eyes. Issue 6 (June 2015) - Estrovich, Igor E.; Shen, Chris; Chu, Yvonne; Downs, J. Crawford; Gardiner, Stuart; Straiko, Michael; Mansberger, Steven L.
Abstract : Purpose: To evaluate the location of the eye and tonometry device that provides the most accurate intraocular pressure (IOP) measurements in eyes with Boston type 1 keratoprosthesis. Methods: A single surgeon sutured a Boston keratoprosthesis into the central cornea in the usual manner in 5 eyes of deceased donors. Another investigator used a 27-gauge needle, digital manometry, and gravity infusion to set the IOP at levels of 10, 20, 30, and 40 mm Hg in random order. A second investigator masked to the level of IOP used a Schiotz tonometer (Sklar) with a 7.5-g plunger load and a Tono-pen XL tonometer (Medtronic) to determine IOP at the temporal corneoscleral limbus and temporal sclera (3 mm temporal to the corneoscleral limbus). We used generalized estimation equation models to determine an average absolute difference between the tonometer measurements compared with the "gold standard" digital manometric IOP. Results: The Schiotz tonometer had a lower median absolute error compared with the Tono-pen at both temporal sclera (5.4 mm Hg vs. 39.0 mm Hg, P < 0.001) and corneoscleral limbus (4.9 vs. 15.0 mm Hg, P = 0.03). The median absolute error for Schiotz was similar at the temporal sclera and corneoscleral limbus ( P = 0.44). Conclusions: The Schiotz tonometer has the highest accuracy of IOP compared with the Tono-pen and gold standard digital manometry. Clinicians could consider Schiotz tonometry when measuring IOP in patients with keratoprosthesis.